Professional personality profiling for purpose of project success in Jabatan Kerja Raya - Mohd. Idris, Nurmawaddah (2015)
The purpose of this study is to identify personality type of project director which will contribute to the project success. The aim of the study is to determine and give a suggestion to top management JKR the suitable personality type of project director which can contribute the project success. The objectives of this paper are to identify the personality type in list of project success in JKR, to assess the project success based on manager’s perception, to determine correlation between personality type and project success and to determine the influence between personality type and project success. The survey method is used in this study and was distributed to 90 respondents and 73 respondents required in this study. The respondents are selected among the professional and management category ranging from grade J54 to J41 of project team which won the Project Management Best Practice Award in JKR in each categories of award. Data gathered from questionnaire will be analyses using descriptive statistic method (mean, median, percentage and standard deviation) and inferential statistics (Pearson Correlation and Multiple Regressions). From the analysis, it showed that current personality among Project Director are conscientiousness personality, agreeableness personality and openness personality. Project success definition in JKR can be determine as a project completed by managing project risks efficiently, by proper and conducive project plan, with minimum or agreed upon scope changes, at the proper performance or specification level and with acceptance by the customer/user. The correlation between personality and project success showed relationship with openness personality, extroversion personality, and emotional stability personality. In determining the influence between personality and project success it showed less influence with personality. But openness personality showed influence in project success